Nano-formulation of a photosensitizer using a DNA tetrahedron and its potential for in vivo photodynamic therapy. (17th December 2015) - Kim, Kyoung-Ran; Bang, Duhee; Ahn, Dae-Ro
Abstract : Photodynamic therapy (PDT) is a cytotoxic treatment using singlet oxygen produced by photosensitizers. Abstract : Photodynamic therapy (PDT) is a cytotoxic treatment using singlet oxygen produced by photosensitizers. Approved porphyrinoid PDT still suffers from a lack of robust production methods and low water solubility. Methylene blue (MB) is a good candidate for the PDT drug, because the dye is an effective photosensitizer, can be easily synthesized, and is already being used in other clinical fields. However, its poor cell/tissue penetration and low stability against the reducible biological conditions should be addressed by using a proper delivery vehicle. Here, we employed a DNA tetrahedron, a self-assembled nanostructure as the carrier for intracellular delivery of MB by taking advantage of the DNA binding property of the photosensitizer and demonstrated photo-induced cytotoxicity by the MB delivered by the DNA nanocarrier. We also evaluated the PDT potency of the MB-loaded DNA nanoconstruct in vivo tumor model to suppress tumor growth.